PENGUATAN HAK BERDAULAT (SOUVEREIGN RIGHT) PADA ZEE INDONESIA DALAM RANGKA PERLINDUNGAN SUMBER DAYA ALAM LAUT - Indien Winarwati (Legality : Jurnal Ilmiah Hukum, 2016)
Sea is a important region for the integrity and unifying, a means of defense and security and foremost as a means of prosperity and welfare of a country due to the potential of the marine resources. Geographically, Indonesia can be termed as a maritime nation. Indonesia has the largest sea area in the world where two-thirds of its territory is waters. Indonesian Exclusive Economic Zone (EEZ) is a maritime area that has the greatest wealth potential. To Regulate, protect and enforce the law in the EEZ, the Indonesian government enacted Law No. 5 of 1983 on the Indonesian Exclusive Economic Zone. In that regulation, there is a provision on the sovereign rights as contained in the provisions of UNCLOS (United Nations Convention on the Law of the Sea). Such right is a privilege rights to carry out the exploration, exploitation and conservation of marine resources. To that end, these rights should be used optimally in order to utilize and protect marine resources from illegal fishing by foreign vessels that have been so frequent that it can be utilized for the welfare and prosperity of society.